The best minds eaudiobook A story of friendship, madness, and the tragedy of good intentions. - Rosen, Jonathan (Books on Tape, 2023)
PULITZER PRIZE FINALIST •  Named a Top 10 Best Book of the Year by The New York Times , The Wall Street Journal , The Atlantic , Slate , and People One of Barack Obama's Favorite Books of 2023 “Brave and nuanced . . . an act of tremendous compassion and a literary triumph.” — The New York Times “Immensely emotional and unforgettably haunting.” —The Wall Street Journal Acclaimed author Jonathan Rosen’s haunting investigation of the forces that led his closest childhood friend, Michael Laudor, from the heights of brilliant promise to the forensic psychiatric hospital where he has lived since killing the woman he loved. A story about friendship, love, and the price of self-delusion, The Best Minds explores the ways in which we understand—and fail to understand—mental illness. When the Rosens moved to New Rochelle in 1973, Jonathan Rosen and Michael Laudor became inseparable. Both children of college professors, the boys were best friends and keen competitors, and, when they both got into Yale University, seemed set to join the American meritocratic elite.   Michael blazed through college in three years, graduating summa cum laude and landing a top-flight consulting job. But all wasn’t as it seemed. One day, Jonathan received the call: Michael had suffered a serious psychotic break and was in the locked ward of a psychiatric hospital.   Diagnosed with paranoid schizophrenia, Michael was still battling delusions when he traded his halfway house for Yale Law School. Featured in The New York Times as a role model genius, he sold a memoir, with film rights to Ron Howard. But then Michael, in the grip of an unshakeable paranoid fantasy, stabbed his girlfriend Carrie to death and became a front-page story of an entirely different sort.   Tender, funny, and harrowing by turns, The Best Minds is Jonathan Rosen’s magnificent and heartbreaking account of good intentions and tragic outcomes whose significance will echo widely.